Artificial Soft–Rigid Protective Layer for Dendrite‐Free Lithium Metal Anode - Xu, Rui; Zhang, Xue‐Qiang; Cheng, Xin‐Bing; Peng, Hong‐Jie; Zhao, Chen‐Zi; Yan, Chong; Huang, Jia‐Qi (Advanced functional materials, 2018)
Lithium (Li) metal has been pursued as “Holy Grail” among various anode materials due to its high specific capacity and the lowest reduction potential. However, uncontrolled growth of Li dendrites and extremely unstable interfaces during repeated Li plating/stripping ineluctably plague the practical applications of Li metal batteries. Herein, an artificial protective layer with synergistic soft–rigid feature is constructed on the Li metal anode to offer superior interfacial stability during long‐term cycles. By suppressing random Li deposition and the formation of isolated Li, such a protective layer enables a dendrite‐free morphology of Li metal anode and suppresses the depletion of Li metal and electrolyte. Additionally, sufficient ionic conductivity is guaranteed through the synergy between soft and rigid structural units that are uniformly dispersed in the layer. Dendrite‐free and dense Li deposition, as well as a greatly reduced interfacial resistance after cycling, is achieved owing to the stabilized interface, accounting for significantly prolonged cycle life of Li metal batteries. This work highlights the ability of synergistic organic/inorganic protective layer in stabilizing Li metal anode and provides fresh insights into the energy chemistry and mechanics of anode in a working battery. An artificial protective layer based on the manipulation in the mechanical properties of soft–rigid and organic–inorganic hybrids is proposed for safe lithium metal anodes. The soft organic or polymeric materials offer stretchability to tolerate the volume fluctuation, while the rigid inorganic materials provide mechanical reinforcement and suppress the growth of lithium dendrites.